2018
DOI: 10.1002/cphc.201800695
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Reagent Interactions Contributing to Ionic Liquid Solvent Effects on a Condensation Reaction

Abstract: Molecular dynamics simulations of solutions of hexan-1-amine or 4-methoxybenzaldehyde in acetonitrile, an ionic liquid/ acetonitrile mixture (c IL = 0.2), and a number of different (neat) ionic liquids were performed, to further understand the solvent effects on the condensation reaction of these species. This work indicates that, in the presence of an ionic liquid, the amine group of hexan-1-amine is exclusively solvated by the components of the ionic liquid, and not by acetonitrile, and that the anion intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…One key consideration, however, is how the ionic liquid solvent is organized around the protein (Hayes et al, 2015; Sprenger et al, 2017). Beyond the demonstrated impact of these interactions in creating the initial solubilisation, as noted through the extensive experimental work in this review, it has been well established that the organization of an ionic liquid around a potential reactive center plays a significant role in directing reactions at that center (Yau et al, 2008, 2009a,b, 2012, 2013; Tanner et al, 2013a,b; Keaveney et al, 2016, 2017, 2018; Hawker and Harper, 2018; Hawker et al, 2018; Schaffarczyk Mchale et al, 2018; Gilbert et al, 2019). The surface site interactions, leading to potential inner site interactions if hydrogen bonds are disrupted, are governed by the relative affinity of the ionic liquid ions for specific amino acids (Sprenger et al, 2017).…”
Section: Future Of Proteins and Enzymes In Ionic Liquidsmentioning
confidence: 97%
“…One key consideration, however, is how the ionic liquid solvent is organized around the protein (Hayes et al, 2015; Sprenger et al, 2017). Beyond the demonstrated impact of these interactions in creating the initial solubilisation, as noted through the extensive experimental work in this review, it has been well established that the organization of an ionic liquid around a potential reactive center plays a significant role in directing reactions at that center (Yau et al, 2008, 2009a,b, 2012, 2013; Tanner et al, 2013a,b; Keaveney et al, 2016, 2017, 2018; Hawker and Harper, 2018; Hawker et al, 2018; Schaffarczyk Mchale et al, 2018; Gilbert et al, 2019). The surface site interactions, leading to potential inner site interactions if hydrogen bonds are disrupted, are governed by the relative affinity of the ionic liquid ions for specific amino acids (Sprenger et al, 2017).…”
Section: Future Of Proteins and Enzymes In Ionic Liquidsmentioning
confidence: 97%
“…22,23 Some scholars added organic solvents to facilitate the rapid separation of condensation products and catalysts to maintain the catalyst activity. 24 However, the use of organic solvents has been known to cause environmental pollution and extra energy consumption in the isolation of products from solvents. It is reported that adjusting the pore size of the catalyst support can enhance the diffusion of condensation products.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic analysis of a variety of ionic liquids on a range of different reactions (examples include: alkyl substitution, [10][11][12][13][14][15][16][17][18][19][20] aromatic substitution, 21-30 condensation [31][32][33] and pericyclic [34][35][36][37][38][39][40] processes) has provided a greater understanding of the effects of ionic liquids on reaction outcomes. Analysis of similar reaction types has shown the solvent effects are predictable, with specific ionic liquids able to be chosen to control reaction outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of similar reaction types has shown the solvent effects are predictable, with specific ionic liquids able to be chosen to control reaction outcome. 25,26,41 These analyses have identified some key interactions of the components of ionic liquids with species along the reaction coordinate, 3 involving both starting materials (aromatic systems [24][25][26]29,30 and lone-pairs 18,19,30,31,33,42,43 ) and transition states. [16][17][18][19][20]24 An example of a reaction that has been examined extensively in ionic liquids is the bimolecular nucleophilic substitution (S N 2) reaction between benzyl bromide 1 and pyridine 2 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%